The Significance Of Foreign Manpower Use Via Government Regulation 34 Of 2021: A Case Study Of Siyasah Dauliyah - Sulaiman, Sri Wahyuni (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2021)
Foreign Workers are inextricably linked to problems and, as documented in the Makassar City Manpower Office's violation data, there are three things that are problematic. First, the Employer does not pay taxes. Second, the prohibition on the use of personnel positions. Thirdly, visa abuse. This is a field study utilizing a syar'i and sociological juridical approach. The study gathered data through primary sources, namely interviews, and secondary sources, namely the examination of legal materials and literature. The study's findings reveal that the usage of foreign workers leads in a high number of offenders in Makassar City, one of which is a lack of monitoring. This is due to the Pora Team's lack of firmness in dealing with field violations and factors from employers of foreign workers who do not comply with required requirements, one of which is avoiding required fees, which is permitted under the legal siyasah dauliyah as long as the service commodities traded do not contain harmful substances. with regard to QS. An-Nisa/4:29 Keywords: Foreign; Use; Labor